The end of the tour [videorecording (DVD)] - Eisenberg, Jesse, 1983-; Segel, Jason, 1980-; Chlumsky, Anna; Gummer, Mamie, 1983-; Lipsky, David, 1965- (Lionsgate, 2015)
The story of the five-day interview between Rolling Stone reporter David Lipsky and acclaimed novelist David Foster Wallace, right after the publication of Wallace's groundbreaking epic novel, 'Infinite jest.' Based on David Lipsky's critically-acclaimed memoir "Although of course you end up becoming yourself: a road trip with David Foster Wallace."